A Time to Sleep Well and Be Contented: Time Perspective, Sleep Quality, and Life Satisfaction - Rönnlund, Michael; Åström, Elisabeth; Westlin, Wendela; Flodén, Lisa; Unger, Alexander; Papastamatelou, Julie; Carelli, Maria Grazia (Frontiers in Psychology, 2021)
This study aimed to examine the relationship between time perspective, i.e. habitual ways of relating to the past, present, and future, and sleep quality. A second aim was to test a model by which the expected negative relationship between deviations from a balanced time perspective (DBTP), a measure taking temporal biases across all three time frames into account, and life satisfaction was mediated by poor sleep quality (cf. Rönnlund & Carelli, 2018b). To these ends, a sample of younger adults (N = 386) completed a version of the Zimbardo Time Perspective Inventory (S-ZTPI), Pittsburg Sleep Quality Index, and the Satisfaction with Life Scale. A measure of circadian preference was in addition included for control purposes. Bivariate analyses revealed that the S-ZTPI subscales Past Negative, Future Negative and Present Fatalistic were associated with poorer sleep quality (higher PSQI scores), with significant associations in the opposite direction for Past Positive and Future Positive. However, DBTP was the strongest predictor of (poor) sleep quality, suggesting that time perspective biases have an additive effect impaired sleep quality. Regression analyses with PSQI as the dependent variable and all six ZTPI subscale as the predictors account for about 20% of the variance in sleep quality, with Past Negative, Past Positive, and Future Negative as the unique predictors. The results additionally confirmed a strong relationship between DBTP and life satisfaction. Finally, data were consistent with the hypothesis that the relation of DBTP and life is mediated, in part, by sleep quality. Taken together, the results confirmed a substantial link between time perspective sleep-related problems, factors that may have a negative impact on life satisfaction.